A sickle cell disease patient with dural venous sinus thrombosis: a case report and literature review. (4th May 2019) - Wang, Michael K.; Shergill, Ravi; Jefkins, Matthew; Cheung, Jason
Abstract: Dural venous sinus thrombosis (DVST) is a rare disease associated with hypercoagulable states. Patients with sickle cell disease are known to be prothrombotic. We report a case of DVST presenting with anterior neck and facial pain in a 24-year-old female with sickle cell disease, found to have extensive thrombotic disease involving the internal jugular vein. A literature review of DVST in sickle cell disease consisting of 14 case reports was summarized. Headache was a presenting feature in two-thirds of patients. Nine cases were associated with vaso-occlusive crisis (VOC), transfusion, or acute respiratory illness. Most patients were treated with anticoagulation therapy. Over three-quarters either died or suffered from a serious neurological complication, including stroke, seizure, coma, or elevated intracranial pressure. Given its association with life-threatening complications, DVST should be considered when patients with sickle cell disease present with a VOC, especially in the context of headache or neurological deficits.